Relationships between anaerobic performance, field tests and game performance of sitting volleyball players - Marszalek, J.; Molik, B.; Gomez, M. A.; Skucas, K.; Lencse-Mucha, J.; Rekowski, W.; Pokvytyte, V.; Rutkowska, I.; Kazmierska-Kowalewska, K. (Journal of Human Kinetics, 2015)
The aim of this study was to evaluate relationships between anaerobic performance, field tests, game performance and anthropometric variables of sitting volleyball players. Twenty elite Polish sitting volleyball players were tested using the 30 s Wingate Anaerobic Test for arm crank ergometer and participated in six physical field tests. Heights in position to block and to spike, as well as arm reach were measured. Players were observed during the game on the court in terms of effectiveness of the serve, block, attack, receive and defense. Pearson analysis and the Spearman's rank correlation coefficient were used. The strongest correlations were found between the chest pass test and mean power and peak power (r=.846; p=.001 and r=.708; p=.0005, respectively), and also between the T-test and peak power (r= -.718; p=.001). Mean power correlated with the 3 m test (r= -.540; p=.014), the 5 m test (r= -.592; p=.006), and the T-test (r= -.582; p=.007). Peak power correlated with the 3 m test (r= -.632; p=.003), the 5 m test (r= -.613; p=.004), speed & agility (r= -.552; p=.012) and speed & endurance (r=-.546; p=.013). Significant correlations were observed between anthropometric parameters and anaerobic performance variables (p=.001), and also between anthropometric parameters and field tests (p=.05). Game performance and physical fitness of sitting volleyball players depended on their anthropometric variables: reach of arms, the position to block and to spike. The chest pass test could be used as a non-laboratory field test of anaerobic performance of sitting volleyball players.